Erfolgsfaktoren für die Beteiligung forstlicher Akteure an der integrierten ländlichen Entwicklung - Das Beispiel LEADER+ Programm der EU-Strukturpolitik - Ortner, Maximilian (Universitätsverlag Göttingen, 2008)
The European Union underlines the growing importance of integrated rural development (ILE). Maximilian Ortner shows how forestry can successfully participate in this development. Forest model projects for drinking water, wood mobilization, increase in sales of wood, energy out of wood, forest preservation or airport environmental education are analyzed as examples of acts of the forestry practice in the context of integrated rural development. The examples are based on the state forests, local forest, private forest owners and the Chamber of Agriculture. About the identified success factors inform a "checklist" with the chance of success of specific projects can be assessed quickly.